Speech Therapy to Overcome Language Disorders in Autistic Children - Yanti, Yunita Novita; Jannah, Septya Sabilatil; Nadia, Soviana; Wahdaniyah, Inayatul; Mutmimah, Mutmimah (GENIUS: Indonesian Journal of Early Childhood Education, 2022)
Some children with autism spectrum symptoms have impaired language skills, resulting in impaired communication skills. They tend to be challenging to develop according to their age, like other children, due to their limitations. But that doesn't mean there isn't anything we can't do. Continuous stimulation through speech and language skills therapy is one of the essential things they need to take so that they can reduce the disorders experienced by these children. This study focuses on describing the stimulation of language development in children with symptoms of autism disorders and knowing what activities can stimulate language skills in children with autism disorders. The approach used in this research is a descriptive qualitative approach. Data mining techniques included interviews and observations at a school for children with special needs. The results of this study indicate that the stimulation of language skills in children with autism disorders can be done with speech therapy to help them develop language skills.   Abstrak Beberapa anak dengan gejala spektrum autisme mengalami gangguan kemampuan berbahasa yang mengakibatkan kemampuan komunikasinya terganggu. Ia cenderung sulit berkembang sesuai usianya seperti anak-anak lainnya disebabkan oleh keterbatasannya tersebut. Namun bukan berarti tidak ada hal yang bisa diupayakan. Stimulasi yang berkesinambungan melalui terapi kemampuan berbicara dan berbahasa merupakan salah satu hal penting yang perlu ditempuh agar gangguan yang dialami oleh anak-anak tersebut dapat berkurang. Tujuan penelitian ini berfokus untuk mendeskripsikan tentang stimulasi perkembangan bahasa pada anak dengan gejala gangguan autisme dan mengetahui kegiatan apa saja yang mampu menstimulasi kemampuan berbahasa pada anak dengan gangguan autisme. Pendekatan yang digunakan pada penelitian ini adalah pendekatan kualitatif deskriptif. Teknik penggalian data yang dilakukan antara lain wawancara dan observasi pada sebuah sekolah anak berkebutuhan khusus. Hasil penelitian ini menunjukkan bahwa stimulasi kemampuan berbahasa pada anak dengan gangguan autisme dapat dilakukan dengan terapi wicara untuk membantu mereka dalam mengembangkan kemampuan berbahasa.